1995
DOI: 10.1002/ajim.4700270602
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of scheduled bright light and darkness on rotating shiftworkers: Trial and limitations

Abstract: The effectiveness of a program of scheduled bright light and dark to alter the circadian pacemakers of rotating shiftworkers were evaluated. Thirteen industrial workers were exposed to scheduled bright light of 6,000-12,000 lux on at least half of their 12-hr night shifts for 3 months, as well as ambient light of 1,200-1,500 lux. All 10 workers evaluated with urinary melatonin levels had morning melatonin suppression on the night shift, and 50% had a statistically significant circadian change. Although a few s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…Some adverse effects were reported, including insomnia and headache from Modafinil (63,65), and nausea, anxiety, low-back pain, and other effects from Armodafinil (64). Adverse events were also reported across other intervention types such as headaches or feelings of heat/cold in response to bright light exposure (29,30), and difficulty scheduling social or family activities as a result of a shift schedule change (39,41), Several studies stated that no significant adverse events resulted from the interventions (35,36,46,61,62), but most did not report adverse events at all. Since participants were not monitored for adverse health effects beyond the study period in all articles, we could not evaluate potential long-term negative health consequences of the interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some adverse effects were reported, including insomnia and headache from Modafinil (63,65), and nausea, anxiety, low-back pain, and other effects from Armodafinil (64). Adverse events were also reported across other intervention types such as headaches or feelings of heat/cold in response to bright light exposure (29,30), and difficulty scheduling social or family activities as a result of a shift schedule change (39,41), Several studies stated that no significant adverse events resulted from the interventions (35,36,46,61,62), but most did not report adverse events at all. Since participants were not monitored for adverse health effects beyond the study period in all articles, we could not evaluate potential long-term negative health consequences of the interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Wearing blue-blocking goggles while commuting improved total sleep time (34) and sleep efficiency (35) in two studies. The two remaining studies found no significant effect of bright light on sleep parameters (24,29).…”
Section: Controlled Light Exposurementioning
confidence: 94%
See 1 more Smart Citation
“…These studies all indicate the heterogeneity of circadian adaptation to night shift work where progressive reduction of morning cortisol levels is consistent with some degree of circadian adaptation to a night oriented schedule 15,75) . Adaptive phase delays of cortisol and melatonin rhythms to an atypical work schedule are possible 76) and are influenced by the pattern of light and darkness exposure 17,75,[77][78][79][80][81][82][83][84] . The pattern of light exposure in night shift workers who spontaneously adapt to the shift work schedule are notable for the stability of sleep times 13) , limited exposure to bright sunlight in the morning 17) , brighter light during shift hours combined with sleep times in darkness 81) , and limited exposure to light throughout the day in Antarctic studies 85) .…”
mentioning
confidence: 99%
“…A major complaint about the use of bright light in the field was that it made the readjustment to a daytime schedule after night work more difficult 21) . This presumably interferes with workers's social and family commitments during their time off.…”
Section: A Lightmentioning
confidence: 99%